Admission Resting Heart Rate as an Independent Predictor of All-Cause Mortality in Elderly Patients with Hip Fracture - Wang Z (Dove Medical Press, 2021)
Zhicong Wang,* Xi Chen,* Yuxuan Wu,* Wei Jiang, Ling Yang, Hong Wang, Shuping Liu, Yuehong Liu Orthopaedic Center of Deyang City, Department of Orthopedics, Deyang People’s Hospital, Deyang, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shuping Liu; Yuehong LiuOrthopaedic Center of Deyang City, Department of Orthopedics, Deyang People’s Hospital, No. 173 Taishan North Road, Jingyang District, Deyang, 618000, People’s Republic of ChinaTel +86 838 241 8102Fax +86 838 241 8102Email doctorliushuping@126.com; doctorliuyuehong@163.comPurpose: To investigate the relationship between admission resting heart rate (RHR) and all-cause mortality in elderly patients with hip fracture.Methods: A retrospective cohort study with 837 patients based on the established hip fracture database was conducted. Admission RHR was measured via electrocardiogram, and patients were grouped by the median RHR value (beats per minute, bpm). The main outcomes were 1-year and total all-cause mortality. Cox proportional hazard models and restricted cubic spline were used to assess the relationship between RHR and mortality. Sensitivity analyses were further performed to determine whether the results were stable.Results: The mean and median RHR were 82.3 and 80.0 bpm, respectively. After a median follow-up of 31.8 months, the 1-year and total all-cause mortality were 17.6% and 31.2%. Multivariable Cox analyses showed that high RHR was an independent risk factor for 1-year mortality (HR = 1.51; 95% CI: 1.08– 2.13; p = 0.016), and total mortality (HR = 1.44; 95% CI: 1.12– 1.85; p = 0.005). For each 10 bpm increase in RHR, the risk of 1-year death increased by 23.0% (HR = 1.23; 95% CI: 1.09– 1.39; p = 0.001), and total death increased by 21.0% (HR = 1.21; 95% CI: 1.09– 1.34; p < 0.001). A typical J-shaped curve was observed in the restricted cubic spline for the association between RHR and 1-year mortality, with the lowest mortality risk at 70 bpm. Sensitivity analyses yielded similar findings.Conclusion: An increase in RHR was independently associated with all-cause mortality, and may be a useful prognostic predictor for elderly patients with hip fracture.Keywords: elderly, hip fracture, resting heart rate, prognosis, mortality